C80 steel fiber high strength concrete
By using copper-plated steel fibers and sustained release water reducing agents in steel fiber concrete, the problem of rapid slump loss of steel fiber concrete is solved, and the high strength and good construction properties of concrete are achieved.
Patent Information
- Application Number
- CN202310293504.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-03-24
- Publication Date
- 2025-03-07
- Estimated Expiration
- 2043-03-24
AI Technical Summary
During the construction process, steel fiber concrete has a rapid slump loss, resulting in a decrease in fluidity and is difficult to level and push, which increases the construction difficulty, and reducing the addition of water reducing agent to slow down the slump loss will affect the strength of the concrete.
Copper-plated steel fibers and sustained-release water reducing agents are used to improve the tensile and crack resistance of concrete. The sustained-release water reducing agent controls the release of water reducing agents through microcapsules to slow down the slump loss of concrete, and the cement hydration speed is increased through the later release of water reducing agents to enhance the compactness and strength of concrete.
It effectively slows down the slump loss of steel fiber concrete, reduces construction difficulty, and ensures the high strength of concrete, reaching compressive strength of C80 and above.
Smart Images

Figure BDA0004142361950000061 
Figure BDA0004142361950000071
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of concrete, and more specifically, to C80 steel fiber high-strength concrete. Background Art
[0002] Steel fiber concrete is a new type of multiphase composite material formed by adding randomly distributed short steel fibers to ordinary concrete. These randomly distributed steel fibers can effectively hinder the expansion of micro cracks inside the concrete and the formation of macro cracks, significantly improving the tensile, bending, impact and fatigue resistance of the concrete, and have good ductility. In the relevant technical field, steel fiber concrete is often used in the construction of roads and bridge decks, but steel fiber concrete has the technical problem of rapid slump loss. The fluidity of concrete decreases rapidly, making it difficult to level and push during construction, thereby increasing the difficulty of construction. In the relevant technology, the slump loss of concrete is slowed down by reducing the addition of water reducers, but this method has an impact on the strength of concrete and its effect is limited. Therefore, it is necessary to develop steel fiber concrete that slows down the slump loss while ensuring the strength of concrete. Summary of the invention
[0003] In order to further slow down the slump loss of steel fiber concrete and ensure the strength of steel fiber concrete, the present application provides C80 steel fiber high-strength concrete and a preparation method thereof.
[0004] The C80 steel fiber high-strength concrete provided in this application adopts the following technical solution:
[0005] C80 steel fiber high-strength concrete, the raw materials include, by weight: 350-450 parts of cement, 600-900 parts of coarse aggregate, 450-550 parts of sand, 200-280 parts of steel slag, 80-140 parts of slow-release water reducing agent, 50-70 parts of copper-plated steel fiber, 180-200 parts of water, and 220-280 parts of fly ash.
[0006] By adopting the above technical scheme, randomly distributed copper-plated steel fibers are added to concrete, which can hinder the extension of small cracks and improve the tensile and crack resistance of concrete. The copper-plated steel fibers have better corrosion resistance and can play the role of steel fibers for a long time to maintain the toughness of steel fiber concrete. By using slow-release water-reducing agent to control the fluidity of steel fiber concrete during the early construction, the loss rate of concrete slump can be slowed down and the construction difficulty can be reduced.
[0007] Preferably, the sand is clean sand that has been surface treated with silicone grease.
[0008] Through the above technical solution, the surface of the sand can be made more lubricated, the friction between coarse and fine aggregates can be reduced, the fluidity of the concrete can be increased, and the slump loss of the steel fiber concrete can be reduced.
[0009] Preferably, the preparation method of the slow-release water-reducing agent is as follows: firstly, the water-reducing agent, calcium aluminate and mica powder are ground into fine powder, passed through a 280-300 mesh sieve, and then granulated, industrial gelatin is sprayed on the outer layer of the particles, and the particles are taken out three times at a weight ratio of 1: (1.5-2.5): 1 at the spraying time of 5-7min, 10-15min and 36-40min to obtain water-reducing agent microcapsules with three self-dissolving film layers of different thicknesses, and finally dried to obtain the slow-release water-reducing agent.
[0010] By adopting the above technical solution, on the one hand, the amount of water-reducing agent released in the early stage is effectively controlled through the intervention of the microcapsule film, which significantly reduces the slump loss; on the other hand, after the capsule is dissolved and released, the water-reducing agent overflows in sequence to control the degree of cement hydration, calcium silicate dissolves and crystallizes, increases the solid phase ratio in the mortar, and the cement stone structure is gradually formed. Calcium aluminate is converted into aluminum-containing precipitates, which fill the original capsule-occupied position in the concrete, repair small gaps, and improve the density and strength of steel fiber concrete.
[0011] Preferably, the self-dissolving film layer of the slow-release water-reducing agent has different thicknesses, and the thickness of the sprayed outer film is 0.05-0.07 mm, 0.09-0.12 mm, and 0.33-0.36 mm.
[0012] By adopting the above technical solution, industrial gelatin has a certain hydrophilicity due to its ether groups, and the thickness of the self-dissolving film layer can be controlled to ensure that the microcapsules exist in the initial state for a suitable time. As the concrete becomes alkaline, the capsules are gradually dissolved and broken in batches.
[0013] Preferably, the water reducer in the slow-release water reducer includes any one or both of lignin sulfonate and polycarboxylate water reducer.
[0014] Preferably, the copper-plated steel fiber is a single-filament hook-end steel fiber that has been copper-plated.
[0015] Preferably, the preparation method of C80 steel fiber high-strength concrete comprises the following steps:
[0016] S1. preparing mixed aggregate: mixing sand and silicone lubricating ester to obtain surface-lubricated sand, and uniformly mixing the surface-lubricated sand, steel slag and coarse aggregate to obtain mixed aggregate;
[0017] S2, preparing a concrete mixture: mixing the pretreated aggregate with the remaining raw materials, and stirring until uniform, to obtain a concrete mixture;
[0018] S3. Preparation of C80 steel fiber concrete: Curing the above concrete mixture to obtain C80 steel fiber concrete.
[0019] In summary, this application has the following beneficial effects:
[0020] 1. This application controls the cement hydration process by adding a slow-release water-reducing agent. By varying the thickness of the slow-release capsule layer, the amount of water-reducing agent released in each period can be adjusted as needed to slow down the rapid loss of slump in the early stage of steel fiber concrete. At the same time, the later release of the water-reducing agent ensures the increase in the cement hydration rate after construction. Finally, calcium aluminate is added to the slow-release water-reducing agent to fill the original space occupied by the slow-release capsule, increase the density inside the concrete, maintain the mechanical properties of the steel fiber concrete, and make the compressive strength reach C80 level or above.
[0021] 2. After the surface treatment, the friction resistance between the fine aggregates in this application is reduced, the flow performance is improved, and the slump of the steel fiber concrete is further maintained stable, which wins more construction time for the steel fiber concrete and greatly reduces the difficulty of construction. DETAILED DESCRIPTION
[0022] The present application is further described in detail below in conjunction with the examples. It is particularly noted that if no specific conditions are specified in the following examples, the experiments are carried out according to conventional conditions or the conditions recommended by the manufacturer. Unless otherwise specified, the raw materials used in the following examples can be obtained from common commercial sources.
[0023] In the following preparation examples and embodiments,
[0024] Use Grade II fly ash for fly ash;
[0025] Steel slag is selected with a particle size of 5-20mm and continuous gradation;
[0026] The sand used is medium sand, with a fineness modulus of 2.6 and a mud content of 1.0%;
[0027] The type of cement is PO52.5;
[0028] The polycarboxylate water reducer in the water reducer adopts the standard polycarboxylate water reducer.
[0029] Preparation example of self-healing gel
[0030] Preparation Example 1
[0031] The preparation method of the slow-release water reducer is as follows: 60kg of polycarboxylate water reducer, 10kg of calcium aluminate, and 10kg of mica powder are ground into fine powder, passed through a 280-mesh sieve, and then granulated, gelatin is sprayed on the outer layer of the particles, and the particles are taken out three times at a ratio of 1:1.5:1 at 5min, 10min, and 36min of spraying time to obtain water reducer microcapsules with three self-dissolving film layers of different thicknesses, and the outer film thickness of the three self-dissolving film layers is 0.05mm, 0.09mm, and 0.33mm. Finally, it is dried to obtain a capsule-type slow-release water reducer.
[0032] Preparation Example 2
[0033] The preparation method of the slow-release water reducer is as follows: 75kg of polycarboxylate water reducer, 20kg of calcium aluminate, and 20kg of mica powder are ground into fine powder, passed through a 280-mesh sieve, and then granulated, industrial gelatin is sprayed on the outer layer of the particles, and the particles are taken out three times at a ratio of 1:2:1 at 6min, 12min, and 38min of spraying time to obtain water reducer microcapsules with three self-dissolving film layers of different thicknesses, and the outer film thickness of the three self-dissolving film layers is 0.07mm, 0.11mm, and 0.35mm. Finally, it is dried to obtain a capsule-type slow-release water reducer.
[0034] Preparation Example 3
[0035] First, 90kg of polycarboxylate water-reducing agent, 30kg of calcium aluminate, and 30kg of mica powder were ground into fine powder, passed through a 300-mesh sieve, and then granulated. Industrial gelatin was sprayed on the outer layer of the particles, and the particles were taken out three times at 7min, 15min, and 40min according to a ratio of 1:2.5:1 to obtain water-reducing agent microcapsules with three self-dissolving film layers of different thicknesses. The thickness of the outer film of the three self-dissolving film layers sprayed was 0.07mm, 0.12mm, and 0.36mm. Finally, the water-reducing agent microcapsules were dried to obtain capsule-type sustained-release water-reducing agent.
[0036] Preparation Example 4
[0037] First, 90 kg of sodium lignin sulfonate and 30 kg of mica powder were ground into fine powder, passed through a 300-mesh sieve, and industrial gelatin was sprayed on the outer layer of the particles. The particles were taken out three times at a ratio of 1:2.5:1 at 7 min, 15 min, and 40 min, and water-reducing agent microcapsules with three self-dissolving film layers of different thicknesses were obtained. The thickness of the outer film of the three self-dissolving film layers was 0.07 mm, 0.12 mm, and 0.36 mm. Finally, the particles were dried to obtain a capsule-type sustained-release water-reducing agent.
[0038] Preparation Example 5
[0039] The water reducer, calcium aluminate and mica powder are ground into fine powder, passed through a 300-mesh sieve and then granulated. Industrial gelatin is sprayed on the outer layer of the particles. The particles are taken out once at 7 minutes after spraying to obtain water reducer microcapsules with a self-dissolving film layer. Finally, the microcapsules are dried to obtain a capsule-type sustained-release water reducer.
[0040] Preparation Example 6
[0041] The water reducer, calcium aluminate and mica powder are ground into fine powder, passed through a 300-mesh sieve and then granulated. Industrial gelatin is sprayed on the outer layer of the particles. The particles are taken out once after the spraying time is 15 minutes to obtain water reducer microcapsules with a self-dissolving film layer. Finally, the microcapsules are dried to obtain a capsule-type sustained-release water reducer.
[0042] Preparation Example 7
[0043] The water reducer, calcium aluminate and mica powder are ground into fine powder, passed through a 300-mesh sieve and then granulated. Industrial gelatin is sprayed on the outer layer of the particles. The particles are taken out once at 40 minutes of spraying time to obtain water reducer microcapsules with a self-dissolving film layer. Finally, the microcapsules are dried to obtain a capsule-type sustained-release water reducer.
[0044] Example of C80 steel fiber concrete
[0045] Example 1
[0046] The preparation method of C80 steel fiber high-strength concrete comprises the following steps:
[0047] S1. Preparing mixed aggregate: mixing 450 kg of sand and 45 kg of silicone lubricating ester to obtain surface-lubricated sand, and uniformly mixing the surface-lubricated sand, 200 kg of steel slag, and 600 kg of coarse aggregate to obtain mixed aggregate;
[0048] S2, preparing concrete mixture: the above pretreated aggregate is mixed with 350kg cement, 80kg slow-release water reducing agent, 50kg copper-plated steel fiber, 220kg fly ash and 180kg water, and stirred until uniform to obtain concrete mixture;
[0049] S3, preparing C80 steel fiber concrete: pouring the above concrete mixture and then curing it to obtain C80 steel fiber concrete.
[0050] Example 2
[0051] The preparation method of C80 steel fiber high-strength concrete comprises the following steps:
[0052] S1. Preparing mixed aggregate: 500 kg of sand and 55 kg of silicone lubricating ester were mixed and stirred to obtain surface-lubricated sand, and the surface-lubricated sand, 240 kg of steel slag, and 750 kg of coarse aggregate were uniformly mixed to obtain mixed aggregate;
[0053] S2, preparing a concrete mixture: mixing the above-mentioned pretreated aggregate with 400 kg of cement, 110 kg of slow-release water reducing agent, 60 kg of copper-plated steel fiber, 190 kg of water, and 250 kg of fly ash, and stirring until uniform to obtain a concrete mixture;
[0054] S3, preparing C80 steel fiber concrete: pouring the above concrete mixture and then curing it to obtain C80 steel fiber concrete.
[0055] Example 3
[0056] The preparation method of C80 steel fiber high-strength concrete comprises the following steps:
[0057] S1. Preparing mixed aggregate: 550 kg of sand and 66 kg of silicone lubricating ester were mixed and stirred to obtain surface-lubricated sand, and the surface-lubricated sand, 280 kg of steel slag, and 900 kg of coarse aggregate were uniformly mixed to obtain mixed aggregate;
[0058] S2, preparing concrete mixture: the pretreated aggregate is mixed with 450 kg of cement, 200 kg of water, 140 kg of slow-release water reducing agent, 70 kg of copper-plated steel fiber, 200 kg of water, and 280 kg of fly ash, and stirred until uniform to obtain a concrete mixture;
[0059] S3, preparing C80 steel fiber concrete: pouring the above concrete mixture and then curing it to obtain C80 steel fiber concrete.
[0060] Example 4
[0061] The method of Example 1 was followed, except that an equal amount of the slow-release water-reducing agent prepared in Preparation Example 1 was replaced by the slow-release water-reducing agent prepared in Preparation Example 4.
[0062] Example 5
[0063] The method of Example 3 was followed, except that an equal amount of the slow-release water-reducing agent prepared in Preparation Example 1 was replaced by the slow-release water-reducing agent prepared in Preparation Example 5.
[0064] Example 6
[0065] The method of Example 3 was followed, except that an equal amount of the slow-release water-reducing agent prepared in Preparation Example 1 in the raw material was replaced by the slow-release water-reducing agent prepared in Preparation Example 6.
[0066] Example 7
[0067] The steps of Example 3 were followed, except that an equal amount of the slow-release water-reducing agent prepared in Preparation Example 1 was replaced by the slow-release water-reducing agent prepared in Preparation Example 7.
[0068] Example 8
[0069] The method of Example 1 is followed, except that the sand in step S1 is replaced by clean sand without surface treatment in equal amount.
[0070] Comparative Example
[0071] Comparative Example 1
[0072] The method of Example 1 is followed, except that an equal amount of mica powder in the raw material is replaced by calcium aluminate.
[0073] Comparative Example 2
[0074] The method of Example 1 is followed, except that the slow-release water-reducing agent in the raw material is replaced by ordinary sodium lignin sulfonate and polycarboxylic acid water-reducing agent in equal amounts.
[0075] Comparative Example 3
[0076] The method of Example 1 is carried out, except that the copper-plated steel fibers in the raw material are replaced by steel fibers that have not been copper-plated.
[0077] Performance testing
[0078] 1. Concrete compressive strength test
[0079] 2. Concrete shrinkage resistance test
[0080] Detection Methods
[0081] 1. Concrete compressive strength test: The steel fiber concrete prepared in the examples and comparative examples was made into 100 mm × 100 mm × 100 mm cubic specimens. According to KGB / T50081-2002 "Standard for Test Methods for Mechanical Properties of Ordinary Concrete", the 7d compressive strength, 28d compressive strength and tensile strength (unit: MPa) of each specimen were tested. The test results are shown in Table 1.
[0082] 2. Concrete slump performance test: The steel fiber concrete prepared in the embodiment and the comparative example was filled into a trumpet-shaped slump bucket with an upper opening of 100 mm, a lower opening of 200 mm, and a height of 300 mm three times. After each filling, a ramming hammer was used to hit the bucket wall evenly from the outside to the inside for 25 times to compact it. Then the slump bucket was pulled up. The steel fiber concrete collapsed due to its own weight. The slump was recorded as the height of the bucket (300 mm) minus the height of the highest point of the concrete after the collapse. The slump data of the steel fiber was tested at 0 min and 50 min after mixing. The test results are shown in Table 2.
[0083] Table 1:
[0084] Test items Example 1 Example 2 Example 3 Example 4 Example 5 Example 6 7d compressive strength / Mpa 46.2 45.4 42.9 42.5 46.6 38.1 28d compressive strength / Mpa 83.4 83.6 84.2 80.0 82.4 83.9 Tensile strength / Mpa 16.9 17.2 17.0 16.6 16.3 16.9 Test items Example 7 Example 8 Comparative Example 1 Comparative Example 2 Comparative Example 3 - 7d compressive strength / Mpa 33.5 45.2 49.5 34.3 32.2 - 28d compressive strength / Mpa 83.1 82.9 83.4 78.9 70.7 - Tensile strength / Mpa 15.9 16.7 16.9 15.7 15.9 -
[0085] Table 2:
[0086]
[0087]
[0088] Combining the performance test results of Example 1, Example 5, Example 6 and Example 7, it can be seen that when all slow-release water-reducing agents with a thinner outer layer are used, the fluidity of the concrete will deteriorate during construction due to the large-scale release of the water-reducing agent in the same period, resulting in slump loss; when all water-reducing agents with a moderate outer layer are used, there is no obvious loss of slump, but the early strength of the concrete will be low, the time for the concrete strength to increase will be increased, and the 28d compressive strength will also decrease slightly; when all slow-release water-reducing agents with a thicker outer layer are used, there is also no obvious loss of slump during construction, but the early strength of the concrete is low, the time for the concrete strength to increase will be greatly increased, and the 28d compressive strength will also decrease slightly.
[0089] Combining the performance test results of Example 1 and Example 8, it can be seen that the flowability of the steel fiber concrete prepared without surface treatment of the sand is poor. Although there is no obvious loss of slump, the initial slump data performance is quite different from that of Example 1, which increases the difficulty of the construction of the steel fiber concrete.
[0090] Combining the performance test results of Example 1 and Example 4, it can be seen that when calcium aluminate is not added to the capsule of the slow-release water-reducing agent, the internal water-reducing agent overflows after the outer layer of the capsule dissolves, and tiny pores formed by the occupied space appear, resulting in the density of the concrete being lower than that of the steel fiber concrete prepared in Example 1. Therefore, the mechanical properties are slightly reduced and the compressive strength is reduced.
[0091] Combining the performance test results of Example 1 and Comparative Example 1, it can be seen that when a non-slow-release water reducer is added, resistance gradually increases during the mixing process, ductility and fluidity gradually decrease during construction, and slump loss is large, resulting in greater construction difficulty.
[0092] Combining the performance test results of Example 1 and Comparative Example 2, it can be seen that the corrosion resistance of concrete made from steel fibers that have not been copper-plated is reduced, and its tensile strength and crack resistance are significantly reduced in its mechanical properties, which does not meet the mechanical performance indicators of C80 grade concrete.
[0093] Combining the performance test results of Example 1 and Comparative Example 3, it can be seen that the cement hydration process of concrete without adding a water reducing agent takes a long time, resulting in a decrease in early strength, and there is also a significant decrease in the 28d compressive strength data, resulting in it not meeting the mechanical performance indicators of C80 grade concrete.
[0094] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.
Claims
1. C80 steel fiber high strength concrete, characterized by: The raw materials include, by weight: 350-450 parts of cement, 600-900 parts of coarse aggregate, 450-550 parts of sand, 200-280 parts of steel slag, 80-140 parts of slow-release water reducing agent, 50-70 parts of copper-coated steel fiber, 180-200 parts of water, and 220-280 parts of fly ash; The sand is clean sand that has been surface treated with silicone lubricating grease; The preparation method of the slow-release water-reducing agent comprises the following steps: firstly, grinding 60-90 parts of water-reducing agent, 10-30 parts of calcium aluminate and 10-30 parts of mica powder into fine powder, passing through a 280-300 mesh sieve and then granulating, spraying industrial gelatin on the outer layer of the particles, taking out the particles three times at a weight ratio of 1: (1.5-2.5): 1 at spraying times of 5-7 minutes, 10-15 minutes and 36-40 minutes, to obtain water-reducing agent microcapsules with three self-dissolving film layers of different thicknesses, and finally drying the microcapsules to obtain the slow-release water-reducing agent; The self-dissolving film layer of the slow-release water-reducing agent has different thicknesses, and the thickness of the sprayed outer film is 0.05-0.07 mm, 0.09-0.12 mm and 0.33-0.36 mm.
2. The C80 steel fiber high-strength concrete according to claim 1, characterized in that: The weight ratio of the added amount of the silicone lubricating grease to the sand is 1:(10-12).
3. The C80 steel fiber high strength concrete according to any one of claims 1 or 2, characterized in that: The water reducer in the slow-release water reducer includes any one or two of lignin sulfonate and polycarboxylate water reducer.
4. The C80 steel fiber high strength concrete according to claim 1, characterized in that: The copper-plated steel fiber is a single-filament hook-end steel fiber that has been copper-plated.
5. The method for preparing C80 steel fiber high-strength concrete according to any one of claims 1 to 4, characterized in that: The preparation method comprises the following steps: S1. Aggregate pretreatment: mixing sand and silicone lubricating ester and stirring to obtain surface-lubricated sand, and uniformly mixing the surface-lubricated sand, steel slag and coarse aggregate to obtain mixed aggregate; S2, preparing a concrete mixture: mixing the pretreated aggregate with the remaining raw materials, and stirring until uniform, to obtain a concrete mixture; S3. Preparation of C80 steel fiber concrete: Curing the above concrete mixture to obtain C80 steel fiber concrete.
Citation Information
Patent Citations
Slow-release microcapsule concrete admixture and preparation method thereof
CN103739223A
Thermal-insulated mortar and preparation method thereof
CN108546150A
Concrete for high-strength PC component and preparation method of concrete
CN112592113A
Environmental complex response homogeneous expansion type self-repairing microcapsule for concrete and preparation method thereof
CN114933441A